Acromegaly and anaplastic astrocytoma: coincidence or pathophysiological relation? - Fernandez, A; Karavitaki, N; Ansorge, O; Fazal-Sanderson, V; Wass, J (2008)
Insulin-like growth factor type I (IGF-I) is an important promoter in the tumorigenesis of several extracranial and intracranial neoplasms. In astrocytic-cell tumors, the role of autocrine and paracrine IGF-I expression in enhancing tumoral progression is well established. However, the influence of systemic IGF-I levels on the clinical behavior of astrocytic neoplasms remains an open subject of research. We report the case of a 28-year-old man who presented simultaneously with acromegaly and an anaplastic astrocytoma, which had rapidly progressed from a low-grade astrocytoma. The coexistence of systemic IGF-I hypersecretion with a quick progression in the histopathological grade of the astrocytoma raises the compelling question of whether the clinical behavior of the astrocytic tumor was influenced by the acromegalic status. The role of IGF-I signaling in the pathogenesis of astrocytic-cell tumors and the experience with therapeutic strategies addressing this pathway in astrocytomas are also discussed.